2020
DOI: 10.1111/jfbc.13515
|View full text |Cite
|
Sign up to set email alerts
|

The hypoglycemic and renal protective effects of Grifola frondosa polysaccharides in early diabetic nephropathy

Abstract: Diabetes mellitus is a group of metabolic diseases in which high blood glucose levels occur over a prolonged period. Hyperglycemia is caused by defective insulin secretion or impaired biological function, whereas long-term hyperglycemia can lead to chronic damage dysfunction of various tissues, especially the eyes, kidneys, heart, blood vessels, and nerves (Home & Home, 2005). According to the World Health Organization, there are more than 100 complications of diabetes. Clinical data have shown that there will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Most of the health-promoting activities are attributed to its content in functional polysaccharides such as β-glucans [14,15], which have been demonstrated to exert antidiabetic properties in both cellular and in vivo models [16]. Thus, different works have reported that the consumption of G. frondosa's body, as well as polysaccharides from this mushroom, exert hypoglycaemic and hypolipidemic effects in high-fat diet (HFD)-and streptozocin (STZ)-induced diabetic rodents [17][18][19][20]. Moreover, this mushroom contains other bioactive molecules, including phenolic compounds, ascorbic acid, α-tocopherol, and flavonoids with antioxidant properties [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the health-promoting activities are attributed to its content in functional polysaccharides such as β-glucans [14,15], which have been demonstrated to exert antidiabetic properties in both cellular and in vivo models [16]. Thus, different works have reported that the consumption of G. frondosa's body, as well as polysaccharides from this mushroom, exert hypoglycaemic and hypolipidemic effects in high-fat diet (HFD)-and streptozocin (STZ)-induced diabetic rodents [17][18][19][20]. Moreover, this mushroom contains other bioactive molecules, including phenolic compounds, ascorbic acid, α-tocopherol, and flavonoids with antioxidant properties [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…Serum creatinine (sCr) and blood urea nitrogen (BUN) are important factors of renal dysfunction, and their levels can reflect the damage degree of the glomerular filtration functions [ 32 ]. They were increased remarkably by 1.7- and 1.3-fold, respectively, in the diabetic group compared to those in the control group ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the hypoglycemic activity of LBP, the diabetic mouse model was established in a similar way as previously described [ 5 , 19 , 31 , 32 ]. Briefly, the mice were randomized into two groups including the control group (fed with normal diet, n = 10) and the HFD group (fed with high-fat diet from Research Diets, D12492, the formulation is showed in Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that MTalpha-glucan has an anti-diabetic effect on KK-Ay mice, which might be related to its effect on insulin receptors (i. increasing insulin sensitivity and ameliorating insulin resistance of peripheral target tissues). Further animal and human experiments also proven that anti-diabetic activity present in the fruit body of G. frondosa [40].…”
Section: Grifola Frondosa (Dicks)mentioning
confidence: 85%